Holistic Approach of Swiss Fetal Progenitor Cell Banking: Optimizing Safe and Sustainable Substrates for Regenerative Medicine and Biotechnology - Laurent, Alexis; Hirt-Burri, Nathalie; Scaletta, Corinne; Michetti, Murielle; de Buys Roessingh, Anthony S.; Raffoul, Wassim; Applegate, Lee Ann (Frontiers in Bioengineering and Biotechnology, 2020)
Safety, quality and regulatory-driven iterative optimization of therapeutic cell source selection has constituted the core innovative developmental bedrock for primary fetal progenitor cell therapy in Switzerland throughout three decades. Customized Fetal Transplantation Programs were pragmatically devised as straightforward workflows for tissue procurement, maximizing traceability, safety, consistency and robustness of progeny cellular materials. Whole-cell bioprocessing standardization has yielded plethoric evidence-based insights into adequate conjugation of modern biotechnological innovation with current legislative, ethical and regulatory constraining frameworks. Pioneer translational advances in cutaneous and musculoskeletal regenerative medicine continuously attest to the considerable therapeutic potential of primary progenitor cells. Extensive technological and clinical hindsight was gathered managing pediatric burns and geriatric ulcers. Concomitant industrial transposition of progenitor dermal fibroblast GMP banking contributed to demonstrate the potential for phenomenal therapeutic value creation. Furthermore, in extenso exponential revalorization of Swiss progenitor cell technology may be achieved throughout establishment of renewed integrative model frameworks. Comprehensive apprehension of both longitudinal and transversal aspects of simultaneous differential processing of specific fetal tissue donations allows to better fathom the quasi infinite expansion potential yielded by tiered primary progenitor cell banking. It is hypothesized that a single qualifying organ donation suffices to aliment decades of scientific, medical and industrial developments, as technological optimization and standardization enable epitomal efficiency. Multiple tissues (e.g. skin, cartilage, tendon, muscle, bone, lung) may be simultaneously harvested and processedfor adherent cell culture, establishing a unique model of sustainable therapeutic cellular material supply chain. This work integrates fundamental, pre-clinical, clinical and industrial implementational developments embodying the scientific breakthroughs supported by Swiss progenitor cell banking. A renewed model of single organ donation bioprocessing is proposed, achieving widespread optimized and standardized sustainability and potential derivation of billions of individual affordable and efficient therapeutic doses. Thereby, the considerable core therapeutic value proposition aims to be substantiated and conveyed for broadening of awareness and use of standardized protocols for translational regenerative medicine, potentially impacting millions of patients suffering from cutaneous and musculoskeletal affections. Alternative applications of primary progenitor cell banking encompass biopharmaceutical therapeutic product manufacture, thereby indirectly and synergistically augmenting the firepower of modern therapeutic armamentariums.